Penatalaksanaan Terapi Latihan Pada Kasus Post Operasi ACL Sinistra Minggu Ke 2 - Nur Iffani Khoirun Nisa; Wijianto Wijianto; Halim Mardianto (Pusat Riset dan Inovasi Nasional, 2024)
The ACL is the most frequently injured knee ligament, accounting for almost half of all knee injuries. from approximately 33 cases in 100,000 in 1994 to between 40 and 60 incidents in 100,000 in 2014. This number is expected to continue to increase as a result of increased participation of adolescents and young adults in athletic activities. The aim of providing interventions is to reduce pain, increase strength muscle, increase muscle strength and to increase the functional activity of the patient and the patient can continue to the next phase of training. In previous studies, physical therapy has been shown to be very important for surgical recovery to regain strength and range of motion. The results obtained were a decrease in pain which was related to an increase in muscle strength, a decrease in pain and an increase in muscle strength influenced the increase in ROM in the knee, which could increase the functional activity of the injured leg.